225 Male Hypogonadism Significantly Increases the Risk of Perinatal Birth Complications: Retrospective Analysis of US Claims Data. Issue 1 (1st April 2022) - Hernandez-Vegas, E; Hotaling, J; Horns, J; Paudel, N; Crump, J; Gross, K; Pastuszak, A; Patel, D
ABSTRACT: Introduction: Hypogonadism is common in men with male factor infertility and hormone therapies may improve semen parameters and pregnancy rates in affected men. However, compared to paternal factors such as advanced age, male infertility or obesity, it is uncertain whether hypogonadism itself impacts perinatal birth outcomes and complications. Objective: This study evaluates the association between male hypogonadism and perinatal birth complications in the United States. Methods: We performed a retrospective analysis of the IBM MarketScan™ Commercial Claims and Encounters database between 2011-2017. We identified birth records using birth or pregnancy-related major diagnostic categories associated with persons age 0. Fathers were considered to be adult (> 18) male individuals with the same family identifier as the neonates listed as either the primary insurance beneficiary or spouse. Birth records were excluded if there was no family identifier or the father was unable to be linked. For each birth, we recorded whether they were preterm, diagnosed as low birth weight, or diagnosed with birth defects. For the fathers linked with each birth record, we determined paternal age, hypogonadism status, geographic region, and other associated comorbidities. Births were stratified based on whether the father had hypogonadism or not and we performed univariate tests for variation. Additionally, we conducted a multivariate logistic model of birth complication (preterm, low weight, or growth defect) against father's age, hypogonadism status, and paternal comorbidities. Results: Between 2011 and 2017, paternal hypogonadism was found in 3.97% of fathers among 468, 546 birth records. In contrast, no paternal hypogonadism was found in 96.03% of fathers among 468, 546 birth records. Overall, our study reveals that paternal hypogonadism is positively associated with perinatal birth complications (odds ratio (OR) 1.10; 95% CI: 1.06, 1.13). Additionally, low birth weight was found in 46, 96% of birth among 196, 607 birth records with paternal hypogonadism, follow by preterm birth with 7.64% of birth among 26, 886 birth records with paternal hypogonadism. Conclusions: Male hypogonadism was associated with a statistically significant increase in perinatal birth complications. However, these results should be interpreted with caution because patients with male hypogonadism are also likely to have male infertility. For hypogonadism to be considered as a separate risk factor for perinatal birth complications further investigation will be needed. Disclosure: No